Gematria e acrostico di Adamo nuovi testimoni - Voicu, Sever J. 1945- (2014)
This note supplements an article on the same subject published in Apocrypha in 2007. It discusses new bibliographical items, but also some previous research which had escaped the author’s attention. Two final paragraphs deal with topics neglected in 2007, namely, the spreading of the acronym across the vernacular languages of Western Europe and its « translation » into Latin, attempted around the year 1200 by Pope Innocent III.